Political connections and stock price crash risk: Empirical evidence from the fall of Suharto - Iman Harymawan; Brian Lam; Mohammad Nasih; Rumayya Rumayya (International Journal of Financial Studies, 2019)
This study examines the relationship between firm-level political connections and stock price crash risk in Indonesia. It employs the difference-in-difference design to deal with the self-selection bias issue regarding the choice of the firms to become a politically connected firm. We use the sudden resignation of the former President of Indonesia, Suharto, to show that politically connected firms are associated with lower stock price crash risk and that the risk for these politically connected firms increased after Suharto resigned. Furthermore, we found evidence that these negative associations are more pronounced in firms with more complex firm structures.
Keywords: D72; G10; L10; 330; complex firm structure; politically connected firms; stock price crash risk